Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division terhadap Pemahaman Konsep Fotosintesis - Putri Heryani, Annisa; Imail, Ali; Syahid, Aah Ahmad (Universitas Negeri Makassar, 2024)
This research is motivated by the use of less varied learning models in learning, especially in science learning, resulting in low student conceptual understanding. The purpose of this study was to determine the effect of using the Student Teams Achievement Division cooperative learning model on students' conceptual understanding. This study used a quasi-experimental research design with a Nonequivalent Control Group. The sample of this study was 61 fourth grade students. Data collection techniques were carried out through conceptual understanding tests. Data analysis used SPSS version 25. The results of the study are as follows: (1) the use of the STAD cooperative learning model in fourth grade students can affect students' conceptual understanding in science subjects, (2) students are active in the learning process after being given treatment. There is an effect on students' conceptual understanding by using the Student Teams Achievement Division cooperative learning model, this is proven through the Effect Size test that the use of the STAD cooperative learning model is able to affect students' understanding in the category of large influence.